A human-rights based approach to Education for All : a framework for the realization of children's right to education and rights within education (UNICEF New YorkUS, 2007)
Presents key issues and challenges in rights-based approaches and provides a framework for policy and programme development from the level of the school up to the national and international levels.
Bibliography : p. 102-107